2021
DOI: 10.1038/s41591-021-01557-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mutant C9orf72 expression by a potent mixed backbone antisense oligonucleotide

Abstract: GGGGCC (G 4 C 2 ) hexanucleotide repeat expansion (HRE) in the first intron of the C9ORF72 (C9) gene is the most common genetic cause of ALS and FTD, two devastating adult-onset neurodegenerative disorders 1,2 . Proposed disease mechanisms include a partial loss of the C9ORF72 protein function (C9ORF72 haploinsufficiency) and acquired toxicity of the repeat expansion 3 . Transcription of the C9ORF72 gene generates three transcript variants: V1, V2 and V3 (Fig. 1a). V1 is translated to produce a short protein i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 51 publications
0
75
0
Order By: Relevance
“…Antisense oligonucleotide (ASO) dependent repeat RNA degradation is promising and realistic therapeutic strategy in C9orf72 FTLD/ALS, 97 and a recent report described a C9orf72 repeat positive ALS patient intrathecally administered with an ASO called afinersen, a newly developed mixed backbone gapmer ASO which selectively targets GGGGCC repeat‐containing C9orf72 transcripts. CSF analysis of this ALS patient revealed dramatic reduction of poly‐GP DPR and partial clinical recovery, suggesting the feasibility of clinical suppression of repeat containing C9orf72 gene through ASO 98 . Meanwhile, BIIB078, another ASO for C9orf72 ALS, was in a phase I clinical trial, but was reported to be discontinued on March 28, 2022, after no efficacy was found in any of the secondary outcomes, although detailed data have not been published.…”
Section: Genetics and Molecular Mechanismsmentioning
confidence: 97%
See 1 more Smart Citation
“…Antisense oligonucleotide (ASO) dependent repeat RNA degradation is promising and realistic therapeutic strategy in C9orf72 FTLD/ALS, 97 and a recent report described a C9orf72 repeat positive ALS patient intrathecally administered with an ASO called afinersen, a newly developed mixed backbone gapmer ASO which selectively targets GGGGCC repeat‐containing C9orf72 transcripts. CSF analysis of this ALS patient revealed dramatic reduction of poly‐GP DPR and partial clinical recovery, suggesting the feasibility of clinical suppression of repeat containing C9orf72 gene through ASO 98 . Meanwhile, BIIB078, another ASO for C9orf72 ALS, was in a phase I clinical trial, but was reported to be discontinued on March 28, 2022, after no efficacy was found in any of the secondary outcomes, although detailed data have not been published.…”
Section: Genetics and Molecular Mechanismsmentioning
confidence: 97%
“…CSF analysis of this ALS patient revealed dramatic reduction of poly-GP DPR and partial clinical recovery, suggesting the feasibility of clinical suppression of repeat containing C9orf72 gene through ASO. 98 Meanwhile, BIIB078, another ASO for C9orf72 ALS, was in a phase I clinical trial, but was reported to be discontinued on March 28, 2022, after no efficacy was found in any of the secondary outcomes, although detailed data have not been published.…”
Section: -C9orf72 Repeat Expansion Mutationmentioning
confidence: 99%
“…An important point to note is that only C9orf72 variants 1 and 3 (which carry the repeat expansion mutation) were targeted by ASOs without affecting variant 2 expression [69]; therefore, C9orf72 abundance post treatment remained fairly similar between transgenic and wild-type animals. Furthermore, another study showed proof of concept in a single human, where intrathecal Afinersen (ASO5-2) was effective at safely suppressing C9orf72 transcripts and had an 80% reduction in poly(GP) dipeptide levels with functional stability in this individual over an 18 month period [70]. Notably, a phase I clinical trial of ASOs targeting C9orf72 variants 1 and 3 (BIIB078) was recently completed by Ionis Pharmaceutical and Biogen Inc., in January 2022, and although it was well tolerated, it did not show any clinical benefit (ClinicalTrials.gov Identifier: NCT03626012) [71].…”
Section: C9orf72mentioning
confidence: 98%
“…Levels of poly(GP) in CSF were not found to correlate with clinical disease markers or neurofilament CSF levels, a non-disease specific biomarker of neurodegeneration 17 24. Encouragingly, ASO treatment of mouse models has been shown to lead to durable, decreased poly(GP) levels both in brain tissues and mouse CSF, and a recent study showed reduction in CSF poly(GP) levels in in a person with C9orf72 ALS, showing that CSF poly(GP) levels could be used as a pharmacodynamic biomarker 16–18 25…”
Section: Introductionmentioning
confidence: 99%